أقوال سيبويه وأثرها في توجيه ق ا رءة نافع من خلال تفسير البحر المحيط لأبي حيان الأندلسي - سورة البقرة أنموذ ج ا - - درويش, أمال; دحمان, تسنيم; قعيد, خديجة (جامعة الوادي university of eloued, 2019)
يتناول البحث دراسة القراءات القرآنية, والذي بعنوان أقوال سيبويو وأثرىا في توجيو قراءة نافع في تفستَ البحر المحيط لأبي حيان الأندلسي ) 745 ه(, سورة البقرة أتفوذجاً. حيث تطرقنا إلى مفاىيم و تعاريف بسيبويو والإمام نافع وقراءتو, وكذلك اتظفسر العظيم الإمام أبي حيان الأندلسي وكتابو التفستَ المحيط. وبتُ البحث القراءة التي أوردىا أبي حيان في سورة البقرة, مع توجيهاتها النحوية واللغوية, بتأثتَ أقوال سيبويو النحوي الذي أعتمد عليو في تفستَه مع ذكر ما يؤيدىا من الشواىد العربية, كما ألقينا الضوء على أقوال سيبويو وأثرىا في توجيو قراءة نافع. بٍ تطرقنا إلى تعريف القراءات والتوجيو ومسألة قواعده في تفستَ البحر المحيط في سورة البقرة وختمنا ىذا البحث بمظاىر تأثتَ أقوال سيبويو وتوجيهها في قراءة نافع رفعا ونصبا وجرا . Summary The study deals with the study of the Qur'an readings, which is titled Sibiu's Sayings and its effect in directing a useful reading in the interpretation of the surrounding sea to Abu Hayyan Al Andalusii (745 AH), Surah Al-Baqarah Where we touched on the concepts and definitions of Psepoye and Imam Nafi and read, as well as the great interpreter Imam Abu Hayyan Andalusia and his book the interpretation of the ocean. The study of the reading, which was narrated by Abo Hayyan al-Baqarah, with its grammatical and linguistic directives, influenced by the words of Sebwayh al-Nahawi, on which Abo Hayyan relied in his interpretation, with the support of the Arab evidence, and shed light on Sibuyah statements. Then we touched on the definition of readings and guidance and the question of its rules in the interpretation of the ocean in the Surat al-Baqarah We concluded this research with the manifestations of the influence of Sayboyeh statements and directing them in the reading of Nafie Raafah, Nisbah and Jara
لغة